Health effects of modern environmental pollution by electromagnetic radiation - Sinaa Fahad Kadhim (Genius Journals, 2023)
Environmental experts have warned of the dangers of electromagnetic waves pollution, which is called pollution electronic is one of the most dangerous types of pollution that has begun to draw attention in recent years. magnetic fields resulting from the construction of giant electric stations as well as radio and television broadcasting antenna towers and in homes where we find electrical devices such as air conditioners, washing machines, fans, televisions, computers and mobile phones, which it has begun to be widely used. All sources of pollution are near us. On the street, we find electric generators in the residential area, high-pressure electricity wires, cellular and wireless communication towers, and electric power0 transformers, as well as from the waves used for medical purposes, which are controlled thanks to advanced technologies, but it is a factor that cannot be forgotten. The waves and electromagnetic fields emanating from these sources fill the atmosphere around us, and the secret of their danger lies in their ability to penetrate the bodies of living things and interact with living cells. This study aims to review the health damages of electromagnetic wave devices to come up with results and recommendations that guarantee the safety and security of humans from the danger of radiation and in what is appropriate for our current reality
Keywords: Electromagnetic radiation; health symptoms; exposures ranging.